Revitalisation Recess as Conflict Resolution and Participation in Physical and Sports Activities - Gema Castillo-Rodríguez; Celestino Carlos Picazo-Córdoba; Pedro Gil-Madrona (Universidad Nacional, Costa Rica, 2018)
This research paper aims to see to what extent a project of revitalization of playgrounds contributes to improving coexistence, conflict resolution, and the participation of boys and girls in sport and physical activities. The paper also aims to know the level of motivation and interest the project could have for the students. For this, after initial assessment, a project of revitalization of recreations was designed, and after a few days of training, it was implemented for a month in a primary school in Spain, with 179 students (98 boys and 81 girls) from 1 to 6 grades; it was carried out in the school playground during a 30-minute recess period. The project consisted of two phases of training; the first one explained different games through training days; the second phase featured free recreation and independent work. The project opted for a mixed methodology of collecting information; this methodology included an information questionnaire and participant observation. The study concludes by highlighting the students' high interest and motivation, the increasing participation, both boys and girls in physical and sports activities, and the reduction of conflicts between students of the center.